Dithionite and sulfinate complexes from the reaction of SO2 with decamethylsamarocene. (16th April 2015) - Klementyeva, Svetlana V.; Arleth, Nicholas; Meyer, Karsten; Konchenko, Sergey N.; Roesky, Peter W.
Abstract : The reaction of [(η 5 -C5 Me5 )2 Sm(THF)2 ] with SO2 resulted in dithionite, sulfinate and mixed dithionite–sulfinate complexes. Abstract : The reaction of [(η 5 -C5 Me5 )2 Sm(THF)2 ] with SO2 resulted in four different products. The dimeric samarium complex [{(η 5 -C5 Me5 )2 Sm(C5 Me5 SO2 )}2 ] (1 ) crystallized from the reaction mixture first. The dithionite–sulfinate complex [{(η 5 -C5 Me5 )2 Sm(S2 O4 )}2 {(η 5 -C5 Me5 )Sm(C5 Me5 SO2 )}2 ] (2 ), was obtained as the second major product after workup of the filtrate. Additionally, the dithionite complex [{(η 5 -C5 Me5 )2 Sm}2 (S2 O4 )] (3 ) and the sulfinate complex [{(η 5 -C5 Me5 )Sm}2 (C5 Me5 SO2 )4 ] (4 ) were isolated as minor products. All compounds were characterized by single crystal X-ray diffraction. As major reaction pathways, the reductive coupling of two SO2 molecules to form the dithionite anion S2 O4 2− and the nucleophilic attack of one samarocene C5 Me5 ligand on the sulfur atom of SO2 were observed.